An In-Vitro Comparative Evaluation of Shear Bond Strength of ChemFil Superior, Cention-N, Giomer and Zirconomer as Restorative Materials in Class-V Lesions - Geeta Nishad; Shripriya Rahane; Nivedita Jaipuriar; Poonam Bhagat; Suyash Thakur; Syed Owais Ahmed (Journal of Pharmacy and Bioallied Sciences)
Background: The success of restorative materials in Class V lesions depends significantly on their adhesive properties. The objective was to assess the shear bond strength of Zirconomer, Giomer, Cention-N, and ChemFil Superior as restorative materials in Class-V lesions. Methods: The following restoration methods were used for the forty removed maxillary central incisor teeth (n = 10): Centri-N, Zirconomer, Giomer, and ChemFil Superior Glass Ionomer Cement. There was thermocycling. The universal testing m shear bond strength analysis was used for all of the specimens. A one-way analysis of variance (ANOVA) and Tukey’s post hoc test were used for statistical analysis. A P value below 0.05 was considered statistically significant. Results: Cention-N had the highest shear bond strength, according to the results. Chemfil had the poorest performance. Conclusion: Cention N had the highest shear bond strength when compared to Zirconomer, Giomer, and ChemFil Superior Glass Ionomer Cement.